ANALISIS PENGARUH BIAYA KESEJAHTERAAN KARYAWAN, BIAYA KEMITRAAN DAN BIAYA BINA LINGKUNGAN TERHADAP ROA PADA BUMN (PERSEROAN) YANG TERDAFTAR DI BEI PERIODE 2010-2014 - Mimelientesa Irman, Juliyanti (Fakultas Ekonomi Universitas Pasir Pengaraian, 2017)
This study aimed to analyze and examine the influence of welfare employee cost, partnership cost, and environment development cost either simultaneously or partially on ROA at BUMN which listing on BEI at 2010 until 2014. Based on the results of the study showed that the variables simultaneously welfare employee cost, partnership cost, and environment development cost significant effect on ROA. The variables partially welfare employee cost and partnership cost significant effect on ROA even though environment development cost unsignificant effect on ROA.